Geothermal well test analysis : fundamentals, applications and advanced techniques - Zarrouk, Sadiq J.; McLean, Katie (Academic Press, 2019)
'Geothermal Well Test Analysis: Fundamentals, Applications and Advanced Techniques' provides a comprehensive review of the geothermal pressure transient analysis methodology and its similarities and differences with petroleum and groundwater well test analysis. Also discussed are the different tests undertaken in geothermal wells during completion testing, output/production testing, and the interpretation of data. In addition, the book focuses on pressure transient analysis by numerical simulation and inverse methods, also covering the familiar pressure derivative plot. Finally, non-standard geothermal pressure transient behaviors are analyzed and interpreted by numerical techniques for cases beyond the limit of existing analytical techniques. -- Provided by publisher.
Includes index.
Keywords: Geothermal wells -- Testing.; Geothermal resources.; Geothermal engineering.; elektronické knihy; electronic books